Shielded metal arc welding rod, its manufacturing method, and shielded metal arc welding method
Patent Information
- Application Number
- JP2021021937
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-09
- Filing Date
- 2021-02-15
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-02-15
AI Technical Summary
【0017】 本発明によれば、再アーク性及び絶縁性が共に優れた被覆アーク溶接棒及びその製造方法、並びに被覆アーク溶接方法を提供することができる。
Smart Images

Figure 0007633037000001 
Figure 0007633037000002 
Figure 0007633037000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a covered metal arc welding rod (hereinafter also simply referred to as "welding rod") used for welding general structures using mild steel such as light-gauge steel frames in shipbuilding, architecture, vehicle manufacturing, etc., a manufacturing method thereof, and a covered metal arc welding method using the covered metal arc welding rod. [Background technology]
[0002] Generally, in the manufacture of ships, buildings, vehicles, etc., there are many places where covered electrodes are used because they are easy to weld in all positions. In covered electrodes, a cylindrical part called a protective tube is formed at the tip of the welding rod during welding because the coating melts later than the core wire, and this protective tube remains at the tip of the welding rod after welding is temporarily interrupted. When welding is resumed, the protective tube is brought into contact with the workpiece (hereinafter also referred to as the "base material") to regenerate the arc. Therefore, when the coating has low electrical conductivity, the protective tube itself generally has low electrical conductivity, and there is a problem that the arc is difficult to regenerate. Hereinafter, the ease with which an arc regenerates after the arc is interrupted during welding is referred to as "re-arcing ability."
[0003] A common method for improving the re-arcing property is to add a highly electrically conductive metal powder to the coating. Conventionally, it has been known to add iron powder to the coating, which also has the effect of increasing the deposition rate and improving welding efficiency. The more iron powder is added to the coating, and the finer the particle size of the iron powder, the higher the electrical conductivity of the coating.
[0004] However, if a large amount of iron powder is added with emphasis on re-arcing properties, the electrical conductivity of the coating material becomes excessively high, making it difficult to ensure sufficient insulation as a covered electrode. When the insulation is reduced, a phenomenon commonly referred to as side arcing, which occurs when the outer surface of the coating material comes into contact with the base metal, becomes more likely to occur. In addition, when using a welding power source that does not have an electric shock protection device, there is a problem that the risk of electric shock to the welder increases.
[0005] Therefore, various covered electrodes have been proposed in order to achieve both excellent re-arcing properties and insulation properties. For example, Patent Document 1 discloses that the content, average particle size, and specific surface area of iron powder in a coating material are specified, and this makes it possible to obtain a low-hydrogen covered metal arc welding electrode that has excellent insulating properties of the coating material, further excellent re-arcing properties, and good welding workability. Furthermore, Patent Document 2 discloses a low-hydrogen tack welding rod in which the contents of metal carbonates, metal fluorides, iron powder, and organic matter in the coating are limited, and the coating rate, the insulation resistance between the steel core wire and the tip of the coating tube, and the insulation resistance between the steel core wire and the coating are limited. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-226779 [Patent Document 2] JP 2004-306094 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, as described above, there is a trade-off between re-arcing property and insulation property. Even when the welding rod described in Patent Document 1 or 2 is used, the re-arcing property is insufficient, and there is a need for a shielded metal arc welding that is excellent in both re-arcing property and insulation property.
[0008] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a covered metal arc welding electrode having excellent re-arcing properties and insulation properties, a method for manufacturing the same, and a covered metal arc welding method. [Means for solving the problem]
[0009] The above object of the present invention is achieved by the following configuration [1] relating to a covered electrode for metal arc welding. [1] A covered metal arc welding rod having a core wire and a coating material that covers the core wire, The coating agent is prepared by adding iron powder having a volume average particle size of 200 μm or less when mixing the raw materials, Based on the total mass of the coating material, Metallic Fe: 30.0% by mass or more and 55.0% by mass or less, CO2: 3.5% by mass or less; When the total Ca in the coating agent is expressed as CaO converted value in mass % relative to the total mass of the coating agent as [CaO], and the total Ti in the coating agent is expressed as TiO2 converted value in mass % relative to the total mass of the coating agent as [TiO2], [CaO] / [TiO2]: 0.5 or less; A covered metal arc welding rod, characterized in that the total mass of the coating material relative to the total mass of the covered metal arc welding rod is 36 mass % or more and 50 mass % or less.
[0010] The above object of the present invention can be achieved by the following configuration [2] relating to another covered electrode. [2] A covered metal arc welding rod having a core wire and a coating material that covers the core wire, Based on the total mass of the coating material, Metallic Fe: 30.0% by mass or more and 55.0% by mass or less, CO2: 3.5% by mass or less; When the total Ca in the coating agent is expressed as CaO converted value in mass % relative to the total mass of the coating agent as [CaO], and the total Ti in the coating agent is expressed as TiO2 converted value in mass % relative to the total mass of the coating agent as [TiO2], [CaO] / [TiO2]: 0.5 or less, The average particle size of the circle equivalent diameter of the iron powder contained in the coating material in a cross section perpendicular to the longitudinal direction of the covered electrode is less than 100 μm, A covered metal arc welding rod, characterized in that the total mass of the coating material relative to the total mass of the covered metal arc welding rod is 36 mass % or more and 50 mass % or less.
[0011] Preferred embodiments of the present invention relating to a covered electrode include the following [3] to [6]. [3] When the content of the metal Fe in the coating is expressed as [metal Fe] in mass% relative to the total mass of the coating, and the total mass of the coating is expressed as [coverage] in mass% relative to the total mass of the covered electrode, The covered metal arc welding rod according to [1] or [2], characterized in that [metal Fe] / [coverage ratio] is 0.62 or more and 1.14 or less.
[0012] [4] When the content of the metallic Fe in the coating agent is expressed as [metallic Fe] in mass% relative to the total mass of the coating agent, and the content of the CO2 in the coating agent is expressed as [CO2] in mass% relative to the total mass of the coating agent, The covered metal arc welding rod according to any one of [1] to [3], characterized in that [metallic Fe]×[CO2] / [TiO2]: 9.0 or less.
[0013] [5] The coating agent contains, based on the total mass of the coating agent, The total Ti in terms of TiO2: 10.0 mass% or more and 40.0 mass% or less, The covered metal arc welding rod according to any one of [1] to [4], characterized in that the total Ca is 0.1 mass % or more and 4.0 mass % or less in terms of CaO.
[0014] [6] The coating agent contains, based on the total mass of the coating agent, Total Si in terms of SiO2: 1.0 mass% or more and 20.0 mass% or less, Total Mn converted to MnO: 10.0 mass% or less, Total Al converted to Al2O3: 10.0 mass% or less At least one selected from Na, K, and Li: the total of the total Na in terms of Na2O, the total K in terms of K2O, and the total Li in terms of Li2O is 8.0 mass% or less.
[0015] The above object of the present invention is achieved by the following configuration [7] relating to a method for producing a covered electrode. [7] A method for manufacturing a covered electrode having a core wire and a coating material for coating the core wire, comprising: A step of coating the core wire with the coating material at a coating rate of 36% by mass or more and 50% by mass or less with respect to the total mass of the covered electrode, The coating Agent contains iron powder having a volume average particle size of 200 μm or less, Based on the total mass of the coating material, Metallic Fe: 30.0% by mass or more and 55.0% by mass or less, and CO2: 3.5 mass% or less, When the total Ca in the coating agent is expressed as CaO converted value in mass % relative to the total mass of the coating agent as [CaO], and the total Ti in the coating agent is expressed as TiO2 converted value in mass % relative to the total mass of the coating agent as [TiO2], A method for producing a covered electrode, characterized in that [CaO] / [TiO2]: 0.5 or less.
[0016] The above object of the present invention is achieved by the following configuration [8] relating to a shielded metal arc welding method. [8] A method for shielded metal arc welding, comprising the steps of: welding with a shielded metal arc welding electrode according to any one of [1] to [6]. Effect of the Invention
[0017] According to the present invention, it is possible to provide a covered metal arc welding electrode having excellent re-arcing properties and insulation properties, a method for producing the same, and a covered metal arc welding method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, the embodiment for carrying out the present invention (hereinafter referred to as "the present embodiment") will be described in detail. Note that the present invention is not limited to the embodiment described below, and can be carried out with any modifications within the scope of the gist of the present invention. In addition, in this specification, "to" indicating a numerical range is used to mean that the numerical values before and after it are included as the lower limit and upper limit. Furthermore, in this specification, the term "oxide" refers to one or more of a "single oxide" and a "composite oxide." A "single oxide," for example, for Al, refers to an oxide of Al alone (Al2O3), and a "composite oxide" refers to an oxide containing multiple elements such as Al, Si, and K.
[0019] <1. Shielded metal arc welding electrodes> The covered electrode according to the present embodiment includes a core wire and a coating material that coats the core wire. The coating material and the core wire according to the present embodiment will be described in detail below. In the present embodiment, the content means mass% relative to the total mass of the coating agent unless otherwise specified. In addition, the content of each component of the coating agent may exceed 100 mass% because some components are specified by the converted value from each element due to the constraints of the analysis method.
[0020] [1-1. Coating materials] The inventors have discovered that by (1) adjusting the amount and particle size of iron powder added to the coating, (2) selecting TiO2 and CaO as the oxides added to the coating, (3) suppressing carbonates, and (4) adjusting the coverage rate, it is possible to obtain excellent effects on both re-arcing properties and insulation properties, which are originally in a trade-off relationship.
[0021] Specifically, the inventors have found that by reducing the amount of iron powder and adjusting the particle size to be small, the distance between the iron powder particles dispersed in the coating can be sufficiently secured, and therefore excellent insulation properties can be secured as a covered electrode. The inventors have also found that by adjusting the coating rate to be high, the distance from the outer surface of the coating to the core wire surface becomes long, and therefore excellent insulation properties can be secured as a covered electrode. Although these configurations alone can ensure excellent insulation, it is difficult to ensure excellent re-arcing properties. Therefore, in the covered electrode according to the present embodiment, TiO2 and CaO, which have high melting points and high wettability with molten Fe, are selected as the oxides contained in the covering material. During welding, a protective tube is formed at the tip of the covered electrode. This protective tube becomes very hot due to the arc heat, so it is believed that high melting point oxides remain solid, but the iron powder melts. The coating contains TiO2 and CaO, which have high wettability with molten Fe, so the molten iron powder moves easily inside the hot protective tube and tends to fuse with nearby molten iron powder.
[0022] That is, when the coating is in a low temperature state, a sufficient distance is ensured between the iron powder particles, so that excellent insulation can be ensured. On the other hand, when the coating is in a high temperature state, the iron powder melts, and the adjacent molten Fe fuses together, so that a sufficient electrical path is formed from the tip of the protective tube to the core wire. Note that carbonate is necessary for stable welding in a covered metal arc welding rod, but since oxides with low electrical conductivity are generated in the protective tube by thermal decomposition, the carbonate content is adjusted to be suppressed in the covered metal arc welding rod according to this embodiment.
[0023] The specific components in the coating agent, the reasons for limiting the numerical values of their contents, the coating rate, etc. will be described in more detail below.
[0024] (Metal Fe: 30.0 mass% or more and 55.0 mass% or less) Metallic Fe is a component that increases the deposition rate and improves welding efficiency, and also has high electrical conductivity, making it a component that improves re-arcing properties. If the content of metallic Fe relative to the total mass of the coating material is less than 30.0 mass%, the welding efficiency decreases and good re-arc properties cannot be maintained. Therefore, the content of metallic Fe relative to the total mass of the coating material is set to 30.0 mass% or more, preferably 32.5 mass% or more, more preferably 34.0 mass% or more, and even more preferably 35.0 mass% or more. On the other hand, if the content of metallic Fe relative to the total mass of the coating exceeds 55.0 mass%, the electrical conductivity becomes too high, causing restrikes to occur from other than the tip of the coating, and sufficient insulation cannot be ensured. Therefore, the content of metallic Fe relative to the total mass of the coating is set to 55.0 mass% or less, preferably 52.5 mass% or less, more preferably 48.5 mass% or less, and even more preferably 47.0 mass% or less. The metallic Fe in the coating agent is contained in iron powder, which will be described later, as well as in ferroalloys such as ferromanganese, ferrosilicon, and ferrotitanium, and in reduced ilmenite. The content of metallic Fe relative to the total mass of the coating agent can be determined, for example, by oxidation-reduction titration.
[0025] (Iron powder volume average particle size: 200μm or less) The volume average particle size (hereinafter referred to simply as "MV"; MV is an abbreviation for "Mean Volume Diameter") of the iron powder added when mixing the raw materials for the coating agent, like the metallic Fe content, affects the condition of the protective tube after welding is interrupted and has a significant effect on re-arcing properties. After welding is interrupted, most of the surface of the protective sleeve melts due to the arc heat during welding. However, if the volume average particle size of the iron powder is small, the iron powder is widely dispersed in the coating material, increasing the number density, and the iron powder has more opportunities to come into contact when melting, which promotes the fusion of adjacent molten iron powder particles. Furthermore, the fusion of the molten iron powder particles ensures a sufficient electrical path, improving re-arcing properties. In this embodiment, the iron powder refers to metal powder containing 95% by mass or more of metallic Fe, with the remainder being impurities such as C, Si, Mn, Fe oxide oxidized on the surface of the iron powder, and S and P. From the viewpoint of ensuring good re-arcing properties and insulating properties, the content of iron powder relative to the total mass of the coating agent is preferably 30.0% by mass or more, and more preferably 32.5% by mass or more.
[0026] If the volume average particle size of the iron powder exceeds 200 μm, the number density of the iron powder will be low, and it will be difficult for the molten iron powder to fuse together, making it difficult to form an electrical path from the tip of the protective tube to the core wire, and making it difficult to ensure good re-arcing. Therefore, the volume average particle size of the iron powder added when mixing the raw materials of the coating agent is 200 μm or less, preferably 180 μm or less, and more preferably 150 μm or less. In addition, the lower limit of the volume average particle size of the iron powder is not particularly limited, but from the viewpoint of ensuring sufficient insulation, it is preferably 20 μm or more, more preferably 40 μm or more, and even more preferably 50 μm or more. Furthermore, in this embodiment, the particle size of the iron powder contained in the coating material is preferably at most about 500 μm in order to prevent the coating material from peeling off the core wire.
[0027] The volume average particle size MV (Mean Volume Diameter) is a value calculated from the particle size distribution measured by a particle size distribution analyzer using a laser diffraction / scattering method, the obtained particle size, and the total volume of particles having that particle size, using the following formula (I).
[0028]
number
[0029] In the above formula (I), d1, d2, . . . , d i , ,d k represents the particle size when each particle is arranged in ascending order of particle size, and v1, v2, . . . , v i ,···,v k represents the total volume of particles corresponding to each particle size above.
[0030] (Average diameter of iron powder equivalent to a circle: less than 100 μm) The average particle size of the iron powder in the coating material according to the present embodiment is determined by calculating the average value of the circle-equivalent diameter of the iron powder in a cross section perpendicular to the longitudinal direction of the covered electrode. The circle-equivalent diameter, as defined in JIS Z 8827-1:2018, refers to the diameter of a circle having an area equal to the projected area of the particle, and can be determined by computer image analysis software or the like. If the average circle-equivalent diameter of the iron powder is 100 μm or more, it becomes difficult to ensure good re-arcing properties. Therefore, the average circle-equivalent diameter of the iron powder is set to less than 100 μm, preferably 80 μm or less, and more preferably 75 μm or less. Although the lower limit of the average particle size of the iron powder's equivalent circle diameter is not particularly specified, from the viewpoint of ensuring sufficient insulation, it is preferably 20 μm or more, more preferably 35 μm or more, and even more preferably 45 μm or more. In this embodiment, in order to prevent the coating from peeling off from the core wire, it is preferable that the equivalent circle diameter of the iron powder contained in the coating is about 500 μm at most.
[0031] (CO2: 3.5% by mass or less) In this embodiment, the content of carbonate in the coating agent is defined as the content of CO2. The oxides produced inside the protective tube by the thermal decomposition of carbonates during welding have a lower electrical conductivity than metallic Fe, the main component of the coating material. Therefore, if the CO2 content exceeds 3.5 mass% relative to the total mass of the coating material, re-arcing properties will deteriorate significantly. In addition, if the carbonate content in the coating agent is high, the fluidity of the molten slag becomes too high, making it difficult to form a uniform and well-encapsulated slag, and the slag removability deteriorates, causing slag seizure. Therefore, the CO2 content relative to the total mass of the coating agent is set to 3.5 mass% or less, preferably 2.5 mass% or less, more preferably 2.0 mass% or less, even more preferably 1.0 mass% or less, and even more preferably 0.5 mass% or less. Although there is no particular lower limit for the CO2 content, the carbonate improves the arc blowing and produces gas by thermal decomposition to prevent oxidation and nitridation of the molten metal, so that the CO2 content relative to the total mass of the coating material is preferably 0.1 mass% or more. The CO2 in the coating agent is contained in carbonates such as CaCO3, BaCO3, MgCO3, MnCO3, FeCO3, Na2CO3, and K2CO3.
[0032] In this embodiment, the ratio of the total Ca in terms of CaO to the total Ti in terms of TiO2 relative to the total mass of the coating material is defined. First, the TiO2 equivalent will be described.
[0033] (TiO2 equivalent value: 10.0 mass% or more and 40.0 mass% or less) The inclusion of Ti oxide in the coating maintains sufficient insulation, and contributes to promoting the fusion of molten iron powder inside the protective tube, improving re-arcing. In addition, Ti oxide enables the formation of uniform and well-encapsulated slag, and has the effect of improving slag removability. In addition, since it has the effect of raising the solidification point of slag, it is possible to prevent dripping of molten metal, and facilitate vertical upward welding. In this embodiment, the preferred content of Ti oxide in the coating is specified as the TiO2 equivalent value of Ti. In order to ensure re-arcing and insulation while maintaining superiority in slag removability and facilitating vertical upward welding, the TiO2 equivalent is preferably 10.0 mass% or more, more preferably 17.0 mass% or more. For the same reason, the TiO2 equivalent is preferably 40.0 mass% or less, more preferably 35.0 mass% or less.
[0034] Examples of Ti oxides in the coating agent include rutile, rucoxin, ilmenite, titanium slag, reduced ilmenite, etc. In addition, metal Ti, alloys such as Fe-Ti, etc. may be contained to improve the mechanical properties of the molten metal.
[0035] (CaO equivalent value: 0.1% by mass or more and 4.0% by mass or less) The inclusion of Ca oxide in the coating agent ensures sufficient insulation, and contributes to promoting fusion of the molten iron powder inside the protective tube, improving re-arcing. In addition, Ca oxide enables the formation of uniform and well-encapsulated slag, and has the effect of improving slag removability. In this embodiment, the preferred content of Ca oxide in the coating agent is defined as the CaO equivalent value of Ca. In order to maintain superiority in slag removability while ensuring re-arcing and insulation properties, the CaO equivalent value is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, and for the same reason, is preferably 4.0% by mass or less, more preferably 3.0% by mass or less, even more preferably 2.5% by mass or less, and even more preferably 1.0% by mass or less.
[0036] The Ca oxide source in the coating agent may be CaO, etc., or may be a carbonate of Ca, a silicate of Ca, or a fluoride such as CaF2, which are thermally decomposed during welding to generate CaO in the coating agent. In addition, metal Ca, an alloy such as calcium silicon, etc. may be contained in order to improve the mechanical properties of the molten metal.
[0037] ([CaO] / [TiO2]: 0.5 or less) When a covered electrode is exposed to a high-temperature arc during welding, if the temperature exceeds 1300°C, the Ca oxide and Ti oxide in the coating react to produce highly insulating CaTiO3 at the interface, and necks form between the Ca oxide and Ti oxide. This neck formation inhibits the fusion of the molten iron powder, resulting in poor re-arcing. The above-mentioned neck is caused by the movement of material to the contact points of particles as the particles are heated, and refers to the part where the particles are connected by the material. By reducing the ratio of the CaO equivalent value to the TiO2 equivalent value, it is possible to suppress the generation of CaTiO3, which has high insulation properties, and make it difficult for necks to form. When the CaO equivalent value of all Ca in the coating is expressed as [CaO] in mass % relative to the total mass of the coating, and the TiO2 equivalent value of all Ti in the coating is expressed as [TiO2] in mass % relative to the total mass of the coating, in order to maintain re-arcing properties, [CaO] / [TiO2] is set to 0.5 or less, preferably 0.4 or less, more preferably 0.2 or less, and even more preferably 0.1 or less.
[0038] (Coverage: 36~50% by mass) The coverage rate refers to the ratio (mass%) of the mass of the coating to the total mass of the covered electrode. If the coverage rate is too low, the distance from the outer surface of the coating to the core wire becomes short, resulting in deterioration of insulation. Therefore, the coverage rate is set to 36 mass% or more, and preferably 37 mass% or more. On the other hand, if the coverage is too high, the distance between the tip of the protective tube and the core wire after welding becomes long, and re-arcing becomes poor. Therefore, the coverage is set to 50% by mass or less, preferably 48% by mass or less, more preferably 47% by mass or less, and even more preferably 46% by mass or less.
[0039] ([Metal Fe] / [Covering rate]: 0.62 to 1.14) If the coverage rate is high, the distance between the tip of the protective tube and the core wire after welding will be long, and if the content of metallic Fe in the coating is low, good re-arcing properties cannot be ensured. On the other hand, when the coverage is low, the distance from the outer surface of the coating to the surface of the core wire becomes short, and when the content of metal Fe in the coating is high, good insulation cannot be ensured. Therefore, when the content of metal Fe in the coating is expressed as [metal Fe] in mass% relative to the total mass of the coating, and the total mass of the coating is expressed as [coverage] in mass% relative to the total mass of the covered electrode, in order to further improve re-arcing properties and insulation properties, it is preferable that [metal Fe] / [coverage] is 0.62 or more and 1.14 or less. In order to further improve re-arcing properties, it is more preferable that it is 0.82 or more, and even more preferable that it is 0.85 or more. In order to further improve insulation properties, it is more preferable that it is 1.12 or less, and even more preferable that it is 1.10 or less.
[0040] ([Metal Fe]×[CO2] / [TiO2]: 9.0 or less) If the content of metallic Fe in the coating is expressed as [metallic Fe] in mass% relative to the total mass of the coating, the content of CO2 in the coating is expressed as [CO2] in mass% relative to the total mass of the coating, and the TiO2 equivalent value of all Ti in the coating is expressed as [TiO2] in mass% relative to the total mass of the coating, then if ([metallic Fe] x [CO2] / [TiO2]) is 9.0 or less, it is possible to form a uniform slag with good encapsulation properties, and the slag removability can be further improved. Therefore, ([metallic Fe] x [CO2] / [TiO2]) is preferably 9.0 or less, more preferably 5.0 or less, and even more preferably 4.0 or less.
[0041] (Total Si in terms of SiO2: 1.0% by mass to 20.0% by mass) By including Si in the coating agent, the viscosity of the molten slag is increased, the fluidity is improved, and the bead appearance and bead shape can be improved. In this embodiment, Si may be included in the coating agent as necessary to improve the bead appearance and bead shape. The content of Si relative to the total mass of the coating material is specified as the SiO2 equivalent value obtained by converting the total Si in the coating material into SiO2. When it is desired to increase the viscosity of the molten slag to improve the fluidity and improve the bead appearance and shape, the SiO2 equivalent value is preferably 1.0 mass% or more, more preferably 5.0 mass% or more. For the same reason, the SiO2 equivalent value is preferably 20.0 mass% or less, more preferably 17.0 mass% or less. The Si in the coating agent is contained in Si oxides such as SiO2, Si silicates, metallic Si, alloys such as ferrosilicon, and adhesives such as water glass.
[0042] (Total Mn converted to MnO: 10.0% by mass or less) The inclusion of Mn in the coating material can improve the tensile strength and slag removability of the weld metal. In this embodiment, Mn may be included in the coating material as necessary to adjust the tensile strength and slag removability. The Mn content relative to the total mass of the coating material is specified as an MnO equivalent value obtained by converting the total Mn amount in the coating material into MnO. If the MnO equivalent value is 10.0 mass% or less, it is possible to adjust the tensile strength of the weld metal while suppressing deterioration of other mechanical properties such as toughness and hardness, and good mechanical properties can be obtained, and a value of 8.0 mass% or less is more preferable. Even a small amount of Mn in the coating agent can have the effect of improving slag removability. In order to fully exert this effect, however, the MnO-equivalent value is preferably 0.5 mass % or more, and more preferably 1.0 mass % or more. The Mn in the coating agent is contained in oxides such as MnO, MnO2, Mn3O4, and Mn2O3, Mn sulfides, Mn carbonates, metallic Mn, and alloys such as ferromanganese.
[0043] (Total Al converted to Al2O3: 10.0 mass% or less) By including Al in the coating material, the viscosity of the molten slag can be increased, the fluidity can be improved, and the bead appearance and shape can be improved. In this embodiment, Al may be included in the coating material as necessary to improve the bead appearance and shape. The content of Al relative to the total mass of the coating material is specified as an Al2O3 equivalent value obtained by converting the total amount of Al in the coating material into Al2O3. In order to properly adjust the viscosity of the molten slag, control the fluidity, and maintain good bead appearance and bead shape, the Al2O3 equivalent value is preferably 10.0 mass% or less, and more preferably 8.0 mass% or less. Even a small amount of Al in the coating agent can have the effect of improving the bead appearance and bead shape, but in order to fully exert this effect, the Al2O3 equivalent value is preferably 0.5 mass% or more, and more preferably 1.0 mass% or more. The Al in the coating agent is contained in Al oxides such as Al2O3, metallic Al, alloys such as aluminum-magnesium, and the like.
[0044] (At least one selected from Na, K, and Li (total of total Na in Na2O equivalent, total K in K2O equivalent, and total Li in Li2O equivalent): 8.0 mass% or less) The arc stability can be improved by including at least one selected from Na, K, and Li in the coating material. Therefore, in this embodiment, in order to improve the arc stability, at least one selected from Na, K, and Li may be included in the coating material as necessary. The total content of components selected from Na, K and Li relative to the total mass of the coating material is defined as the total content of the Na2O converted value, the total K converted value and the total Li converted value. Hereinafter, the total content of the Na2O converted value, the K2O converted value and the Li2O converted value is referred to as the R2O converted value. In order to improve the arc stability, the R2O converted value is preferably 8.0 mass% or less, and more preferably 6.0 mass% or less. In addition, even trace amounts of Na, K and Li in the coating material can improve the arc stability. In order to fully exert this effect, the content in terms of RO is preferably 0.5 mass % or more, and more preferably 1.0 mass % or more. The Na, K and Li in the coating agent are contained in oxides such as Na2O, K2O and Li2O, metallic Na, metallic K, metallic Li, Na alloys, K alloys, Li alloys, adhesives such as water glass, etc.
[0045] (C: 5.0% by mass or less) By including C in the coating material, it is possible to increase the blowing force of the arc and improve the welding workability. In this embodiment, in order to increase the blowing force of the arc and improve the welding workability, C may be included in the coating material as necessary. If the C content is 5.0 mass% or less relative to the total mass of the coating material, it is possible to obtain good welding workability while preventing excessive arc spray and an increase in the amount of spatter. Therefore, the C content is preferably 5.0 mass% or less, and more preferably 4.0 mass% or less. Furthermore, even a small amount of C in the coating material can have the effect of improving welding workability, but in order to fully exert this effect, the C content is preferably 0.5 mass % or more. The C in the coating agent is contained in various metals, alloy powder raw materials, or organic matter such as starch and wood powder. In addition, in this embodiment, the "C content in the coating agent" is a value obtained by subtracting the C content in CO2 (the CO2 content multiplied by 0.2727) from the total C content relative to the total mass of the coating agent.
[0046] (Total F amount: 5.0% by mass or less) By including F in the coating material, it is possible to increase the viscosity of the molten slag, improve the fluidity, and improve the bead appearance and bead shape. In this embodiment, F may be included in the coating material as necessary to improve the bead appearance and bead shape and to reduce diffusible hydrogen. The content of fluoride relative to the total mass of the coating agent is defined as the total amount of F in the coating agent. In order to increase the viscosity of the molten slag to improve the fluidity and improve the bead appearance and shape, the total amount of F in the coating agent is preferably 5.0 mass% or less, more preferably 4.0 mass% or less. Even a small amount of F in the coating agent can have the effect of improving the bead appearance and bead shape, but in order to fully exert this effect, the total F content is preferably 0.1 mass % or more, and more preferably 0.2 mass % or more. In addition, F in the coating material is contained in CaF2, BaF2, MgF2, AlF2, K2SiF6, Na2SiF6, etc.
[0047] (Total value of each component composition including converted values) In this embodiment, the sum of the metallic Fe, CO2 content, Ti in terms of TiO2, Ca in terms of CaO, total Si in terms of SiO2, total Mn in terms of MnO, total Al in terms of Al2O3 and R2O relative to the total mass of the coating agent shown above is preferably 86 mass% or more, more preferably 88 mass% or more, and even more preferably 90 mass% or more, from the viewpoint of obtaining good slag removability and bead shape.
[0048] (Other ingredients) In this embodiment, the coating agent may contain Fe oxides, Fe sulfides, Fe carbonates, etc., in addition to the above-mentioned components. The Fe contained in the Fe oxides, Fe sulfides, Fe carbonates, etc. is preferably 7 mass% or less based on the total mass of the coating agent. The coating agent may further contain at least one element selected from Mg, Ba, Zr, B, Ni, Cr, Mo, V, Cu, etc., and each of Mg, Ba, Zr, B, Ni, Cr, Mo, V, Cu, etc. is preferably 3 mass% or less based on the total mass of the coating agent.
[0049] (impurities) Other elements contained in the coating material include unavoidable impurities such as P. From the viewpoint of ensuring welding quality such as hot cracking resistance, the content of P relative to the total mass of the coating material is preferably suppressed to 0.5 mass% or less. Also, the total value of impurities relative to the total mass of the coating material is preferably suppressed to 3 mass% or less.
[0050] [1-2. Core wire] The type of core wire in this embodiment is not particularly limited, but for example, one having a diameter d of 2.6 mm to 6.0 mm can be used, and in particular, one having a diameter of 3.2 mm or 4.0 mm can be suitably used. The components contained in the core wire according to this embodiment and the preferred contents thereof will be described below.
[0051] (O: 0.0005 mass% or more, 0.0500 mass% or less) If the core wire has an excessive O content, the amount of O in the obtained weld metal will be excessive, which may reduce the toughness of the weld metal. Furthermore, the fluidity of the molten metal increases, and dripping of the weld metal is likely to occur in welding in a vertical position, overhead position, etc., which may reduce the efficiency of welding. Therefore, the O content of the core wire is preferably 0.0500 mass% or less, more preferably 0.0300 mass% or less, and even more preferably 0.0150 mass% or less, relative to the total mass of the core wire. On the other hand, if the O content of the core wire is too low, the molten pool is not sufficiently stirred by the arc force, and a weld metal in which the alloy components are uniformly distributed cannot be obtained. Therefore, the O content of the core wire is preferably 0.0005 mass% or more, more preferably 0.0013 mass% or more, and even more preferably 0.0016 mass% or more, based on the total mass of the core wire.
[0052] (Other Ingredients) In this embodiment, the other components of the core wire are not particularly limited, but for example, an iron-based core wire whose main component is Fe can be suitably used, and specifically, SWRY11 specified in JIS G 3503:2006 can be used as the core wire. In addition to the above O and Fe, the core wire may contain C, Si, Mn, P, S, N, Cu, etc. It is preferable that the C content of the core wire is 0.09 mass% or less, the Si content is 0.10 mass% or less (including 0 mass%), the Mn content is 0.35 mass% to 0.65 mass%, the P content is 0.040 mass% or less (including 0 mass%), the S content is 0.035 mass% or less (including 0 mass%), and the Cu content is 0.20 mass% or less (including 0 mass%) relative to the total mass of the core wire.
[0053] The covering material and the core wire according to the present embodiment have been described above. As described above, by appropriately controlling the volume average particle size of the iron powder in the coating, the content of the components, and the coverage, it is possible to obtain a covered electrode that is excellent in re-arcing, insulation, and slag removability and is suitable for vertical up welding. Note that the covered electrode according to the present embodiment is particularly suitable for use in vertical up welding, but is not limited to this welding position and can be applied to all positions of welding.
[0054] <2. Manufacturing method of covered metal arc welding electrodes> The method for producing a covered metal arc welding rod according to the present embodiment is a method for producing a covered metal arc welding rod having a core wire and a coating material that coats the core wire, A step of coating the core wire with the coating material at a coating rate of 36% by mass or more and 50% by mass or less with respect to the total mass of the covered electrode, The coating Agent contains iron powder having a volume average particle size of 200 μm or less, Based on the total mass of the coating material, Metallic Fe: 30.0% by mass or more and 55.0% by mass or less, and CO2: 3.5 mass% or less, When the total Ca in the coating agent is expressed as [CaO] in terms of CaO, which is the mass % relative to the total mass of the coating agent, and the total Ti in the coating agent is expressed as [TiO] in terms of TiO2, which is the mass % relative to the total mass of the coating agent, [CaO] / [TiO2]: 0.5 or less.
[0055] The covered metal arc welding electrode according to this embodiment described in <1. Covered metal arc welding electrode> above can be manufactured by blending raw materials for the coating agent so that the coating agent has the above-mentioned component composition, kneading the mixture together with a predetermined adhesive, applying the mixture to the surface of a predetermined core wire so that the coating rate is in the range of 36 mass % or more and 50 mass % or less with respect to the total mass of the covered metal arc welding electrode, and drying the mixture. In the method for producing a covered metal arc welding electrode according to the present embodiment, the type of core wire, the type of adhesive, the method for forming the coating, and the like are not particularly limited, and normal specifications and conditions for producing a covered metal arc welding electrode can be used.
[0056] <3. Shielded metal arc welding method> The covered metal arc welding method according to this embodiment is a method of welding using the covered metal arc welding electrode according to this embodiment described above in <1. Covered metal arc welding electrode>. In the method for covered metal arc welding according to the present embodiment, various welding conditions are not particularly limited except for using the covered metal arc welding rod according to the present embodiment, and normal conditions for a welding method using a covered metal arc welding rod can be used for the type of base metal, welding voltage, welding current, welding position, etc. EXAMPLES
[0057] Hereinafter, examples of the covered electrode according to the present embodiment will be specifically described in comparison with comparative examples. First, SWRY11 (wire rod for covered metal arc welding rod core wire) specified in JIS G 3503:2006 was subjected to wire drawing and cutting to produce a steel core wire made of carbon steel with a core diameter of 3.2 mm and a length of 350 mm. Next, the raw materials of the coating agent were combined to produce coating agents with various component compositions. The particle size of the iron powder used as the raw material of the coating agent was measured using a commercially available particle size distribution meter using the laser diffraction / scattering method (e.g., Microtrack MT3200 manufactured by Microtrack Bell Co., Ltd. (formerly Nikkiso Co., Ltd.)). Then, the coating material is applied to the surface of the core wire and dried to remove the coating. Agent A covered electrode was prepared by covering a core wire with the above.
[0058] Furthermore, the average particle size of the equivalent circle diameter of the iron powder contained in the coating material was measured for the covered electrode obtained by the above method. Here, the method for measuring the average particle size of the equivalent circle diameter of the iron powder is described below.
[0059] First, the covered electrode was cut in the center in the longitudinal direction, and the electrode was embedded in resin so that the vertical cross section to the longitudinal direction was the observation surface, and observed with a scanning electron microscope (SEM). The observation with the SEM was performed at a magnification of 50 times and an acceleration voltage of 25 kV, and a field of view (2.02 × 1.52 mm, 1280 × 960 pixels) was observed using a back scattered electron (BSE) image. The observation field of view was adjusted so that the ratio of the area occupied by the coating to the total area of the field of view was 50% or more. Thereafter, the cross section of the coating material in the above observation field was subjected to elemental analysis and elemental mapping using energy dispersive X-ray spectroscopy (EDX) to identify the iron powder.
[0060] In addition, the entire image of the composition image of the above observation field was binarized into iron powder and other areas at 1280 x 960 pixels using image analysis software ImageJ (version 1.50i, developed by National Institutes of Health, USA). Then, the total area of iron powder with a circle equivalent diameter of 30 μm or more was divided by the number of iron powder particles with a circle equivalent diameter of 30 μm or more to calculate the average particle size of the circle equivalent diameter of the iron powder. When using the above image analysis software, the binarization threshold value for distinguishing the iron powder from the other areas can be set in the range of 100 to 140, but in this embodiment, the binarization threshold value was set to 125. In addition, since image processing is difficult for iron powder with an extremely fine particle size, in this embodiment, iron powder with a circle equivalent diameter of less than 30 μm was excluded from the measurement target. The threshold value for binarization is not particularly limited, and any threshold value can be set as long as it is possible to distinguish between iron powder and other areas.
[0061] Welding was performed using each of the obtained covered electrodes, and re-arcing properties, insulation properties, vertical upward weldability, and slag removability were evaluated. The welding conditions, evaluation methods, and evaluation criteria are shown in Table 1 below. The components in the coating of each covered electrode, the volume average particle size of the iron powder, the average circle equivalent diameter of the iron powder, and the coverage rate are shown in Tables 2 and 3 below, and the evaluation results are shown in Table 4 below.
[0062] In Tables 2 and 3 below, [CaO] is the value obtained by expressing the CaO equivalent value of all Ca in the coating agent as a mass % relative to the total mass of the coating agent, and [TiO2] is the value obtained by expressing the TiO2 equivalent value of all Ti in the coating agent as a mass % relative to the total mass of the coating agent. [Metal Fe] is the content of metal Fe in the coating agent expressed as a mass % relative to the total mass of the coating agent, and [CO2] is the content of CO2 in the coating agent expressed as a mass % relative to the total mass of the coating agent. [Na2O] is the value of the total Na in the coating agent expressed in Na2O equivalent value as a mass % based on the total mass of the coating agent, [K2O] is the value of the total K in the coating agent expressed in K2O equivalent value as a mass % based on the total mass of the coating agent, and [Li2O] is the value of the total Li in the coating agent expressed in Li2O equivalent value as a mass % based on the total mass of the coating agent. [Covering rate] is the total mass of the coating material expressed as mass % relative to the total mass of the covered electrode.
[0063] [Table 1]
[0064] [Table 2]
[0065] [Table 3]
[0066] [Table 4]
[0067] As shown in Tables 2 to 4 above, inventive examples Nos. 1 to 13, the volume average particle size of the iron powder added when mixing the raw materials for the coating agent was within the range of the present invention, and the metallic Fe, CO2, [CaO] / [TiO2], and coverage rate in the coating agent were also within the range of the present invention, so that both the re-arcing property and the insulation property were excellent, and the sample was rated A or B.
[0068] On the other hand, in Comparative Example No. 14, the volume average particle size of the iron powder added when mixing the raw materials of the coating agent exceeded the upper limit of the range of the present invention, so that the re-arcing property was slightly deteriorated and the sample was given a rating of C. In Comparative Example No. 15, the coverage rate exceeded the upper limit of the range of the present invention, and therefore the re-arcing property was slightly deteriorated and the result was evaluated as C. In Comparative Example No. 16, the coverage was below the lower limit of the range of the present invention, and therefore the insulation properties were deteriorated and the sample was evaluated as D. In Comparative Example No. 17, the content of metallic Fe in the coating material was below the lower limit of the range of the present invention, so that the re-arcing property was slightly deteriorated and the sample was given a rating of C.
[0069] In Comparative Example No. 18, the content of metallic Fe in the coating agent exceeded the upper limit of the range of the present invention, and therefore the insulation properties were slightly deteriorated and the sample was evaluated as C. In Comparative Example No. 19, the coverage was below the lower limit of the range of the present invention, so that the insulation properties were slightly deteriorated and the evaluation was C. In Comparative Example 20, the metallic Fe content was below the lower limit of the range of the present invention, so that the re-arcing property was slightly deteriorated and the sample was given a rating of C.
[0070] In Comparative Example No. 21, the amount of CO2 in the coating agent exceeded the upper limit of the range of the present invention, and therefore re-arcing property was deteriorated and the sample was given a rating of D. In Comparative Example No. 22, the CO2 in the coating agent exceeded the upper limit of the range of the present invention, and the [CaO] / [TiO2] ratio also exceeded the upper limit of the range of the present invention, so that the re-arcing property deteriorated and the sample was evaluated as D.
Claims
1. A covered metal arc welding rod having a core wire and a coating material that covers the core wire, Based on the total mass of the coating material, Metallic Fe: 30.0% by mass or more and 55.0% by mass or less, CO 2 : 3.5% by mass or less, The total Ca content in the coating agent is expressed as [CaO] in mass % relative to the total mass of the coating agent, and the total Ti content in the coating agent is expressed as [TiO]. 2 The converted value is expressed as mass% relative to the total mass of the coating material [TiO 2 ], [CaO] / [TiO 2 ]: 0.5 or less, and The average particle size of the circle equivalent diameter of the iron powder contained in the coating material in a cross section perpendicular to the longitudinal direction of the covered electrode is less than 100 μm, The total mass of the coating material relative to the total mass of the covered electrode is 36 mass% or more and 50 mass% or less; When the content of the metal Fe in the coating agent is expressed as [metal Fe] in mass % relative to the total mass of the coating agent, the total mass of the coating agent is expressed as [coverage rate] in mass % relative to the total mass of the covered electrode, and the content of the CO 2 in the coating agent is expressed as [CO 2 ] in mass % relative to the total mass of the coating agent, [Metal Fe] / [Coverage rate]: 0.62 or more and 1.14 or less, and [Metal Fe] x [CO 2 ] / [TiO 2 ]: 9.0 or less; The coating agent contains, based on the total mass of the coating agent, The total Ti in terms of TiO 2 is 10.0% by mass or more and 40.0% by mass or less, The total Ca content in terms of CaO is 0.1% by mass or more and 4.0% by mass or less, Total Si in terms of SiO 2 is 1.0 mass% or more and 20.0 mass% or less, Total Mn in terms of MnO: 10.0 mass% or less, Total Al content in terms of Al 2 O 3 : 10.0 mass% or less, 1. A covered metal arc welding rod comprising at least one element selected from the group consisting of Na, K and Li, the total of which is a value of total Na converted into Na 2 O, a value of total K converted into K 2 O and a value of total Li converted into Li 2 O being 8.0 mass% or less.
2. A method for manufacturing a covered electrode having a core wire and a coating material that coats the core wire, comprising: The step of coating the core wire with the coating material at a coating rate of 36 mass % or more and 50 mass % or less with respect to a total mass of the covered electrode, The coating agent contains iron powder having a volume average particle size of 200 μm or less, Based on the total mass of the coating material, Metallic Fe: 30.0% by mass or more and 55.0% by mass or less, and CO 2 : 3.5% by mass or less, The total Ca content in the coating agent is expressed as [CaO] in mass % relative to the total mass of the coating agent, and the total Ti content in the coating agent is expressed as [TiO]. 2 The converted value is expressed as mass% relative to the total mass of the coating material [TiO 2 ], [CaO] / [TiO 2 ]: 0.5 or less, When the content of the metal Fe in the coating agent is expressed as [metal Fe] in mass % relative to the total mass of the coating agent, the total mass of the coating agent is expressed as [coverage rate] in mass % relative to the total mass of the covered electrode, and the content of the CO 2 in the coating agent is expressed as [CO 2 ] in mass % relative to the total mass of the coating agent, [Metal Fe] / [Coverage rate]: 0.62 or more and 1.14 or less, and [Metal Fe] x [CO 2 ] / [TiO 2 ]: 9.0 or less; The coating agent contains, based on the total mass of the coating agent, The total Ti in terms of TiO 2 is 10.0% by mass or more and 40.0% by mass or less, The total Ca content in terms of CaO is 0.1% by mass or more and 4.0% by mass or less, Total Si in terms of SiO 2 is 1.0 mass% or more and 20.0 mass% or less, Total Mn in terms of MnO: 10.0 mass% or less, Total Al content in terms of Al 2 O 3 : 10.0 mass% or less, A method for producing a covered metal arc welding rod, comprising: at least one selected from the group consisting of Na, K and Li; the total of a value of total Na in terms of Na 2 O, a value of total K in terms of K 2 O and a value of total Li in terms of Li 2 O being 8.0 mass% or less.
3. A method for welding using the covered metal arc welding electrode according to claim 1.
Citation Information
Patent Citations
High-strength low-hydrogen low-alloy-steel iron powder welding electrode with high low-temperature impact resistance and for nuclear grade 1 and preparation method thereof
CN104096986A
JP1970031749Y1
Covered arc welding rod
JP1979135640A
Coated arc electrode
JP1980161596A
Low hydrogen system covered arc welding rod
JP1999226779A